Investment and investment finance in Europe - Atanas Kolev; Tanja Tanayama; Rien Wagenvoort (European Investment Bank (EIB), 2013)
Combining in-house research and work by leading academics, this report assesses how the crisis has impacted investment across the non-financial sector, in small and medium-sized enterprises (SMEs), in infrastructure, and in R&D and innovation. It explains why and where investment has declined, looking at the impact of structural imbalances, policy uncertainty, new capital requirements for banks and the fragmentation of Europe's financial markets. In terms of policy options, it warns against poorly targeted responses and provides, instead, support for key policy interventions at the European level.
Keywords: 330; investment; economic recession; small and medium-sized enterprises; economic infrastructure; research and development; innovation; investment policy